Literature Review on Islamic Social Finance as An Instrument of Food Security - Intan Fatkhuroh Hikmah; Muhamad Subhi Apriantoro (Universitas Muhammadiyah Surakarta, 2025)
Purpose: This study aims to identify and analyze the main research themes in Islamic Social Finance literature published in internationally reputable journals, in order to understand the focus and direction of existing scholarly work. Methodology: The study employs a systematic literature review (SLR) approach. A total of 26 journal articles were collected, screened, and classified into thematic categories related to Islamic Social Finance. Results: The findings reveal that research on Islamic Social Finance is predominantly focused on general Islamic Social Finance issues, comprising 20 papers (60%). Zakat-related studies account for 3 papers (20%), followed by waqf with 2 papers (15%), and food security with 1 paper (5%). This distribution indicates an imbalance in thematic coverage within the literature. Applications/Originality/Value: This study provides a structured mapping of Islamic Social Finance research themes, offering valuable insights for researchers and policymakers. It contributes original value by highlighting underexplored areas, such as food security, which may serve as potential directions for future research and policy development in Islamic Social Finance.